DIAGNOSTIC VALUE OF ULTRASOUND EXAMINATION IN PREOPERATIVE STAGING OF DISSEMINATED OVARIAN CANCER - N. V. Vyatkina; I. G. Frolova; L. A. Kolomiets; S. V. Molchanov; A. B. Villert (Сибирский онкологический журнал, 2016)
The aim of the study was to compare the efficacy of the optimized ultrasound technique with the use of additional methods (change in the patient’s body position, forced type of breath and abdominal scanning with high-frequency probes) for assessing the preoperative staging in 47 patients with primary epithelial ovarian cancer. It was shown that the optimized ultrasound technique, especially in cases with low-volume ascites, allowed improvement in preoperative staging of ovarian cancer, with sensitivity of 87%.